POLEX-SOUTH DATA, PART 1 : RADIATION DATA AT MIZUHO STATION, ANTARCTICA IN 1979 - YAMANOUCHI, Takashi; WADA, Makoto; MAE, Shinji; KAWAGUCHI, Sadao (National Institute of Polar Research, 1981)
P(論文) departmental bulletin paper